O riso do antropófago: cumplicidade e dissidência na estética de Oswald de Andrade - Bertelli, Giordano Barbin (2014)
This study proposes two main tasks: one of them aims at the exercise of experimenting a sociological perspective to fit the questioning of a certain general image regarding the social; the other task is to be consistent to the first, and links to an effort to pull the literary phenomenon to apprehend it from the Literature universe itself. In part, we tried to outline an approach to minimize the reifying effects that accompany the conception of social, when it overlays the primacy of order, stability and systematicity. On the other end, the essay of a literary text reading which, to some extent, took us to rethink the status of the expressive form in relation to other forms overall, the discussion of the properly political place occupied by the literary esthetics in discursive disputes on the definition of parameters regarding the order and the legitimate social life. The analytical focus is centered on poetic procedures of Oswald de Andrade s Anthropophagy, regarding its relations (firstly) with the paulista nationalism that was elaborated in the First Republic, and (secondly) with the expressive and performative regimes of marginalized groups. These regimes happened in the historical developments of the Abolition, the immigration and the urban expansion in São Paulo in the late 19th and early 20th centuries. Upon the approach to humorous and obscene aspects of Oswaldian writings, we discuss the relationship between social process, subjectivity and literary elaboration, as a way to provide the access to the relationships between aesthetics and politics, without postulating a deterministic unilateralism of the social order over literature, and without reducing the literary aesthetics to politicalpamphleteering instrumentality.